Transient Musical Hallucinations in a Young Adult Male Associated with Alcohol Withdrawal - Blackman, Graham; Lim, Mao Fong; Mannan, Fahmida; David, Anthony (Case Reports in Psychiatry, 2019)
We present the case of a 25-year-old male who presented to A&E with isolated musical hallucinations, in the absence of audiological or neurological disease. The patient had a history of recreational drug use and a family history of psychosis. Hallucinations, which were preceded by discontinuation of alcohol and reinitiation of citalopram for depression, resolved spontaneously after three days. Aetiological factors are discussed alongside the existing literature. Whilst the underlying mechanisms underpinning musical hallucinations remain elusive, the case illustrates the potential role of alcohol withdrawal, serotonin toxicity, recreational drug use, and genetic vulnerability.